Réponses

2013-10-23T12:28:01+02:00
1) (3x-1) (2x + 5/2) = 0
     SOIT  3x-1 = 0 donc 3x = 1 et x = 1/3
     SOIT  4x +5 = 0 donc 4x = -5 et x = -5/4

2) 25x^2-49=0
     (5x-7)(5x+7) = 0
     SOIT 5x -7 = 0 donc 5x =7 et x = 7/5
     SOIT 5x +7 = 0 donc 5x = -7 et x = - 7/5
3) (x-6) (3x-1) + (x-6)^2 = 0
     (x-6)(3x-1) + (x-6)(x-6) = 0
     soit x-6 = 0 et x = 6
     soit 3x-1 = 0 donc 3x = 1 et x = 1/3

4) 4x-12-(x-3) (2x+4) = 0
     je ne suis pas sûre donc je ne réponds pas 
 
     4x-(3/2 -4x) ≥ -1 +7x

4x - (3 -8x ) > -1+7x
4x - 3 +8x > -1 +7x
4x +8x -7x > -1 +3
5x > 2
x> 2/5